Mount Melbourne Quadrangle, Victoria Land, Antarctica 1:250,000 (Antarctic Geomorphological and Glaciological Map Series). - BARONI, CARLO; SALVATORE, MARIA CRISTINA; BIASINI A.; BONDESAN A.; DENTON G. H.; FREZZOTTI M.; GRIGIONI P.; MENEGHEL M.; OROMBELLI G.; DELLA VEDOVA A. M.; VITTUARI L. (ICSU(FAGS)/IUGG(IACS)/UNEP/UNESCO/ WMO, World Glacier Monitoring Service, 2005)
The geomorphological and glaciological map of the Mt. Melbourne quadrangle (74°–75° S, 162°–166° 30’ E) is the first product of a cartographic project in Victoria Land undertaken by the Italian National Antarctic Research Program (PNRA). The project involves the survey of six maps between the David Glacier (to the south) and Tucker Glacier (to the north) basins. Victoria Land is divided into two distinct regions, one to the north and the other to the south of Terra Nova Bay (located within the Mt. Melbourne quadrangle). Outlet glaciers cross the Transantactic Mountains and drain the East Antarctic Ice Sheet (EAIS) in southern Victoria Land, while an arborescent network of glacial valleys is fed by ice fields and local névées in northern Victoria Land. In the Mt. Melbourne quadrangle, the Priestley and Revees outlet glaciers drain the EAIS (southern portion of the Talos Dome area) and part of the Victoria Land névé (southern part of the Deep Freeze and Eisenhower ranges). Small ice caps and snow fields on the Transantarctic Mountains feed the Campbell, Tinker and Aviator glaciers. The Terra Nova Bay area lies in a very interesting geographic position for characterising the dynamics of present-day glaciers, and periglacial processes acting in deglaciated areas, and for reconstructing the Cenozoic history of the EAIS. Reported geomorphological and glaciological data derives from the analysis of satellite images and aerial photographs, and from field surveys. The main landscapes of the region were surveyed and geometric relationships between different morphologies were analyzed. Besides detailed studies conducted in key sites for depicting the geological and geomorphological evolution of the two sectors of Victoria Land, we applied a method of geomorphological mapping that permits the collection of data in a wide regional context (“regional landscape analysis”).The principal cartographic objectives were: 1) to describe the most relevant components of the landscape, with particular emphasis on modern glaciers and ...